Pemberdayaan Masyarakat Melalui Kegiatan Economic Project Olahan Fish Corndog di Desa Pasir Panjang, Pulau Rinca, NTT - Atfi Indriany Putri; Roudlotul Badi’ah; Muhammad Ikbal Putera; Fahri Ikhlas; Arni Putri Awaliyah Umar (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to diversify processed fishery products as regional souvenirs to attract tourists and increase the selling value of fishery products in Pasir Panjang Village, Rinca Island, West Manggarai Regency, East Nusa Tenggara (NTT) Province. The method used in this service program is counselling and training with a participatory approach. Implementation of service activities includes survey and administration stages, Focus Group Discussion (FGD), implementation, and evaluation based on success indicators determined. The result of this community service activity was the creation of an innovative processed fishery product called